Personal, Socio-economic and Psychological Profile of Integrated Farming System Module Practicing Farmers in North-Eastern Dry Zone (Zone-II) of Karnataka, India - Pradeep Kumar T L; S. B. Goudappa; Shashidhara, K. K; Sidram, B. Y; B. S. Reddy; Umesh, M. R (Archives of Current Research International, 2025)
The Green Revolution’s intensive practices led to soil degradation and land fragmentation continues, reducing farm efficiency. As the population grows, agricultural sustainability faces pressure with declining land and productivity. Small farmers, who make up to 85.00 per cent of the population, struggle with low incomes. Integrated Farming Systems (IFS) are being explored to boost farmers income and promote sustainability through diversified practices. A study conducted in the North-eastern dry zone of Karnataka analysed the profile of Integrated Farming System (IFS) practicing farmers. Among 240 respondents, 53.33 per cent were in the middle age category, followed by 23.33 per cent with pre-university education. The majority (54.17 %) had medium family size and 52.92 per cent had 15-30 years of farming experience. Regarding farm size, 55.83 per cent were medium farmers and 54.58 per cent had medium cropping intensity. Additionally, 54.58 per cent had medium irrigation potential, while 50.83 per cent showed medium innovative proneness. A majority (60.42 %) had medium risk orientation, and 55.83 per cent displayed medium achievement motivation. In terms of management orientation, 47.08 per cent had medium levels, while 51.67 per cent had medium scientific orientation. Furthermore, 52.50 per cent had high decision-making ability, 47.50 per cent had medium mass media exposure, and 52.92 per cent had medium extension participation. Lastly, 42.50 per cent had high economic motivation. These results emphasize the prominence of medium levels across several variables, which are crucial for designing appropriate interventions for IFS adoption.